Self-Employment Problem — the Role and Place of Microenterprises in Regional Economy - Jasińska-Biliczak, Anna (Regional Barometer. Analyses & Prognoses, 2015)
Article’s aim is undertaking the issue of the self-employment as the peculiar form of business activity made exclusively personally by the owner of the enterprise and its conditioning. There also will be discussed this form of the business activity as the sources of innovations, engine of economic and social changes and places where individualists can find employment. There will be indicated the self-employment’s place in the sector of small and medium enterprises and the regional economy as well. For achievement of this aim there will be used the literature review from the scope of the local economy and the small and medium-entrepreneurship as well as undertaking the problem of the self-employment. The legislation being in force, documents of bodies of the European Union as well as documents attesting to the importance of the problem, so as parliamentary questions will be indicated (desk research). There was undertaken the analysis of data corresponding to the self-employment in Opolskie Voivodship having as the aim pointing the problem (data analysis).